III-nitride memristors: materials, devices, and applications - Yang Yang; Haotian Li; Qilin Hua (Materials Futures, 2025)
Memristors, with their compactness, nonvolatile storage, and dynamic resistance modulation, are poised to revolutionize next-generation memory and neuromorphic computing paradigms. III-nitride materials, such as boron nitride (BN), gallium nitride (GaN), and aluminum nitride (AlN), exhibit exceptional properties for advancing memristive technologies, including wide bandgaps (3.4–6.2 eV), high electron mobility (10 ^2 –10 ^3 cm ^2 (V·s) ^−1 ), high thermal conductivity (up to 400 W (m·K) ^−1 ), and robust resistance to harsh environments (e.g. extreme temperatures, radiation). Coupled with inherent complementary metal-oxide-semiconductor (CMOS) compatibility, these attributes position nitride-based memristors as a transformative platform for scalable, energy-efficient, and reliable electronics. In this review, we systematically examine recent advancements in III-nitride memristors, with a focus on materials engineering, device structures, and emerging applications. We begin by outlining the unique advantages of III-nitride materials for memristor design, followed by a critical analysis of progress in BN, GaN, AlN, and AlScN-based devices. We then explore their hardware-level implementations, demonstrating their role in next-generation chip architectures. Finally, we discuss the challenges and future directions to advance nitride-based memristive technologies. Notably, III-nitride memristors unlock unprecedented opportunities for high-performance electronics in extreme environments while bridging the gap between bio-inspired computing paradigms and hardware scalability, enabling adaptive, high-speed, and energy-efficient intelligent systems.